(untitled) - Janda, Petr (Aura musica, 2020)
This study deals with the choral works of the Czech composer Jan Novak (1921-1984), with focus on the 1960s. It points out important elements of Novak's work, such as the metro-rhythmics in conjunction with Latin prosody, demonstrates some typical examples of the composer's musical language and outlines his own ways to deal with the influences of the so-called "New Music". The article also presents a number of authentic expressions of various figures of the musical life, including the composer himself, that contribute to a closer understanding of the character of Jan Novak's work.
Keywords: Jan Novak; composer; choral work; latin; 1960s